Digital Financial Literacy of MSMEs in Emerging Countries: A Systematic Literature Review and Future Research Agenda - Azis, Azolla Degita; Mukminin, Amirul; Zulma, Gandy Wahyu Maulana; Nugraha, Nugraha; Lyndon, Novel Anak (Educational Leadership and Management Journal, 2026)
Digital Financial Literacy (DFL) has gained popularity in academic research over the past ten years, particularly as digital financial services have transformed the way individuals and businesses interact with the economic system. This paper presents a comprehensive systematic literature review (SLR) analysis of digital financial literacy studies in micro, small, and medium enterprises (MSMEs) in developing countries. The analysis uses VOSviewer to map the scholarly community, analyze the topic's evolution, and identify key contributors based on Scopus literature from 2016 to 2026. The number of articles decreased from 7,219 to a target collection of 26 articles using progressive classification. This study creates a conceptual framework for mapping digital financial literacy using the findings of the most cited studies. The result shows financial literacy, acceptance of fintech, digital financial inclusion, and financial risk behaviour are prevalent themes. The literature on digital financial literacy in the MSMEs area is still fragmented and under-theorized, despite the significant increase in academic contributions from emerging countries. In order to strengthen MSME financial resilience in the digital era, this review unifies scattered information and suggests a future research agenda that calls for context specific studies, comparative cross-country analysis, and more policy-oriented inquiry.